Mammalian and yeast U3 snoRNPs are matured in specific and related nuclear compartments - Verheggen, Céline (Oxford University Press, 2002)
Nucleolar localization of vertebrate box C/D snoRNA involves transit through Cajal bodies, but the significance of this event is unkown. To define better the function of this compartment, we analyzed here the maturation pathway of mammalian U3. We show that 3′-extended U3 precursors possess a mono-methylated cap, and are not associated with fibrillarin and hNop58. Importantly, these precursors are detected at both their transcription sites and in Cajal bodies. In addition, mature U3, the core box C/D proteins and the human homolog of the methyltransferase responsible for U3 cap tri-methylation, hTgs1, are all present in Cajal bodies. In yeast, U3 follows a similar maturation pathway, and equivalent 3′-extended precursors are enriched in the nucleolus and in the nucleolar body, a nucleolar domain that concentrates Tgs1p under certain growth conditions. Thus, spatial organization of U3 maturation appears to be conserved across evolution, and involves specialized and related nuclear compartments, the nucleolus/nucleolar body in yeast and Cajal bodies in higher eukaryotes. These are likely places for snoRNP assembly, 3′ end maturation and cap modification.